RNA Fluorescence with Light-Up Aptamers - Ouellet, Jonathan (Frontiers in Chemistry, 2016)
Seeing is not only believing; it also includes understanding. Cellular imaging with GFP in live cells has been transformative in many research fields. Modulation of cellular regulation is tightly regulated and innovative imaging technologies contribute to further understand cellular signaling and physiology. New types of genetically encoded biosensors have been developed over the last decade. They are RNA aptamers that bind with their cognate fluorogen ligands and activate their fluorescence. The emergence and the evolution of these RNA aptamers as well as their conversion into a wide spectrum of applications are examined in a global way.